Gas trapping of hot dust around main-sequence stars. Issue 2 (20th August 2020) - Pearce, Tim D; Krivov, Alexander V; Booth, Mark
ABSTRACT: In 2006, Vega was discovered to display excess near-infrared (NIR) emission. Surveys now detect this phenomenon for one fifth of main-sequence stars, across various spectral types and ages. The excesses are interpreted as populations of small, hot dust grains very close to their stars, which must originate from comets or asteroids. However, the presence of such grains in copious amounts is mysterious, since they should rapidly sublimate or be blown out of the system. Here, we investigate a potential mechanism to generate excesses: dust migrating inwards under radiation forces sublimates near the star, releasing modest quantities of gas that then traps subsequent grains. This mechanism requires neither specialized system architectures nor high dust supply rates, and could operate across diverse stellar types and ages. The model naturally reproduces many features of inferred dust populations, in particular their location, preference for small grains, steep size distribution, and dust location scaling with stellar luminosity. For Sun-like stars, the mechanism can produce 2.2 μ m excesses that are an order of magnitude larger than those at 8.5 μ m, as required by observations. However, for A-type stars the simulated NIR excesses were only twice those in the mid-infrared; grains would have to be 5–10 times smaller than those trapped in our model to be able to explain observed NIR excesses around A stars. Further progress with any hot dust explanation for A stars requires a means for grains to become very hot without either rapidly sublimating or being blown out of the system.